Nilai-nilai Budaya Melayu Dalam Sistem Pemerintahan Kepenghuluan Pada Masyarakat Adat Kampung Kuala Gasib di Kecamatan Koto Gasib Kabupaten Siak - Elmayanti Elmayanti; Ferawati Ferawati (Journal of Education and Culture (JEC), 2021)
With the stipulation of traditional villages in Siak Regency, it certainly has an impact on the administration of government. Fundamental changes are seen in government and community institutions in traditional villages. Regulation Regional Siak No. 2 of 2015 concerning the determination of traditional villages, explains the customary village government institutions where the penghulu is the head of the traditional village. The type of research used in this research is sociological legal research. Traditional villages have a function to organize community life as a legal community unit related to customary law, culture and can be used as a basis for smooth governance and implementation of development. The establishment of this traditional village is one of the objectives to give the broadest authority to the traditional village to maintain customs and territorial rights. The traditional village has the identity of elements as an alliance of customary law communities, and has several characteristics that distinguish it from other social groups which automatically become indigenous peoples. The factors that influence the success of the penghulu government system in the indigenous people of the Kuala Gasib village are the existence of a law that clearly regulates the position of a penghulu, the availability of a budget for development, the existence of adequate facilities and infrastructure in carrying out the wheels of government in the traditional village. In Kuala Gasib, there is a need for an MOU (Memorandum Of Understanding) or legal understanding between the village and the law (police), related to the settlement of crimes or irregularities.